1977
DOI: 10.1002/1097-0142(197709)40:3<987::aid-cncr2820400304>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin, 1,3-bis (2-chloroethyl)-1-nitrosourea (BCNU, NSC 409962) and cyclophosphamide therapy of drug-resistant metastatic breast carcinoma

Abstract: Thirty-two evaluable patients with metastatic carcinoma of the breast received chemotherapy consisting of BCNU plus cyclophosphamide followed in 18 hours by Adriamycin. Treatments were repeated every 4 weeks. Complete or partial responses were observed in 14 patients (43.7%) and in 12 of 27 drug-resistant patients (44.4%). An additional 26% of patients had objective improvement, for an overall objective response rate of 70.4% in drug-resistant patients. Skin, lymph node, and soft tissue metastases more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The drugs are usually chosen for such combinations for the following reasons: (a) they kill cells in different parts of the cell cycle; (b) they do not have overlaping toxicities in normal tissues; (c) their combined effects are synergistic; (d) the individual drugs (used alone) are very effective against a particular tumor; (e) the drugs are schedule dependent (14,16,(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The drugs are usually chosen for such combinations for the following reasons: (a) they kill cells in different parts of the cell cycle; (b) they do not have overlaping toxicities in normal tissues; (c) their combined effects are synergistic; (d) the individual drugs (used alone) are very effective against a particular tumor; (e) the drugs are schedule dependent (14,16,(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous ECOG studies have shown that the addition of Halotestin to CMF maintenance results in longer time to treatment failure. l 3 The combination of dibromodulcitol, Adriamycin, vincristine, tamoxifen, and Halotestin (DAVTH) was piloted at the University of Pretoria (Pretoria, South Africa) and the University of Wisconsin (Madison, WI) with complete and partial responses in 15 of 20 patients within the first 3 months of treatment. 14 Based upon these observations of the effectiveness of both the thiotepa-based regimen and the dibromodulcitolbased regimen, the benefit of Halotestin in giving longer time to treatment failure, the necessity for developing a program for patients who had previously been treated with tamoxifen, and the desirability of having a regimen that would be effective in patients previously treated with CMF, the combination dibromodulcitol, Adriamycin, vincristine, and Halotestin (DAVH) was selected for comparison with TAVH.…”
mentioning
confidence: 99%